STRATEGI PENINGKATAN KUALITAS MEMBACA AL-QUR’AN DENGAN PENDEKATAN ILMU TAJWID DI PONDOK PESANTREN AL-IHSAN KALIJARING JOMBANG - Nur Anita (JoEMS (Journal of Education and Management Studies), 2020)
Al-Qur'an is the holy book which was revealed to the Prophet Muhammad PBUH. Where the Al-Qur'an is a guide for all Muslims who are always sung every prayer. Obligations of Muslims include prayer, where prayer is the base of all Islamic worship. And what if in prayer we are not correct in reciting letters or sentences in the Qur'an ?. That is an example of the importance of studying the science of recitation. And also because it is motivated by the importance of understanding the material of recitation of recitation as the law of reading the Qur'an with recitation of recitation is fardhu ‘ain, especially students are prospective tahfidz in the future. This research is intended to answer the problem: (1) How is the strategy to improve the quality of reading the Qur'an at Al-Ihsan Islamic Boarding School Kalijaring Jombang? (2) How is the application of tajwid science in learning to read the Qur'an at Al-Ihsan Kalijaring Islamic Boarding School in Jombang? These problems were discussed through field study research conducted at Al-Ihsan Islamic Boarding School. Data collection techniques using the method of observation, documentation, interviews. While data analysis techniques use deductive thinking and inductive thinking. The results of this study, namely: (1) how to improve the quality of reading the Qur'an in the Al-Ihsan Islamic Boarding School in a conscious, systematic, planned and focused way on changing the ability of students in mastering good Qur'an reading procedures and true, as for efforts to improve the ability to read the Qur'an through dirosah, curricular activities, the addition of supporting facilities. While the methods used are lectures, questions and answers, dril methods or ready exercises. In studying recitation in the Al-Ihsan Islamic Boarding School using the Tuhfatul Athfal and Matan Jazariyah guidelines, the media used were blackboards, markers and notebooks. (2) the application of tajwid science in learning to read Al-Qur'an at Al-Ihsan Islamic Boarding School is done in groups according to the ability of students in learning to read Al-Qur'an which is carried out after each dawn and maghrib prayer and there is also a question and answer discussion.